Effectiveness of online project-based learning on Chinese EFL learners’ critical thinking skills and reading comprehension ability - Song, Xinke; Razali, Abu Bakar; Sulaiman, Tajularipin; Jeyaraj, Joanna Joseph (Elsevier, 2025)
Critical thinking skills (CTS) and reading comprehension ability (RCA) are crucial for academic success among English as a Foreign Language (EFL) learners. However, many Chinese college EFL learners face challenges in developing these skills due to traditional instructional methods that prioritize teacher-centered learning and rote memorization. Grounded in sociocultural theory (SCT) and Critical Thinking Framework, this study investigates the effectiveness of an online Project-Based Learning (PBL) approach integrated with critical thinking (hereafter referred to as “online PBL”) in enhancing CTS and RCA among Chinese college EFL learners. A pilot study was conducted to evaluate the feasibility of the PBL teaching steps and the reliability of the measurement instruments. Following this, an 11-week quasi-experiment was implemented. The experimental group participated in online PBL, emphasizing student-driven projects, problem solving, and the explicit application of CTS. In contrast, the comparison group followed the traditional Presentation-Practice-Production (PPP) method, which focuses on structured, teacher led presentations and practice. Pre- and post-tests using the International Critical Thinking Reading and Writing Test (ICTRWT) were employed to assess learners’ CTS and RCA. Data analysis through multivariate repeated measures ANOVA indicated statistically significant improvements in the experimental group’s CTS and RCA compared to the comparison group, with moderate to large effect sizes. These findings support the effectiveness of integrating online tools with critical thinking and PBL methodologies in EFL contexts, although the study is limited by its small sample size and single post-test assessment.